Studying the Effects of Various Yeast on the Three-Year Aging Process of Brandy Spirits Made From “Kangun” and “Meghrabuyr”Grape Varieties - Khachatryan, T. L.; Shahinyan, L. V.; Harutyunyan, Sh. H.; Nersisyan, A. H. (ՀԱԱՀ հիմնադրամ)
Brandy spirits, matured for three years and produced with various yeasts, were examined to assess their quality. The study included evaluating sensory indicators and conducting a qualitative and quantitative analysis of volatile aromatic compounds. Results showed that brandy spirits fermented with “Oenoferm Bouquet” yeast, displayed the highest concentrations of volatile aromatic substances, with this variant receiving the most favorable tasting evaluation among the sampled spirits.
Keywords: Food Science and Technology